Effect of Globalization on Unemployment in ASEAN - Iftitah, Maratul; Kusumawardani, Deni (Jurnal Ilmu Ekonomi Terapan, 2022)
In recent decades globalization has become increasingly evolving. The existence of openness between countries facilitates the establishment of mutually beneficial cooperation between various countries. The formation of ASEAN organizations is one example of the existence of globalization. This research aims to analyze the influence of globalization, especially economic, social, political and economic growth and wages on unemployment in ASEAN. This research uses regression analysis of panel data. Zurich and the World Bank in the period 2000-2017. The results of the study concluded that the variables of globalization as a whole, social and political globalization have a significant negative effect on unemployment. The wage control variable has a significant negative effect, while economic growth has a negative but insignificant effect on unemployment. Meanwhile, economic globalization has a positive effect on the unemployment rate in ASEAN.